2019
DOI: 10.1007/s15010-019-01359-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-typeable Haemophilus influenzae-associated early pregnancy loss: an emerging neonatal and maternal pathogen

Abstract: Objectives There is increasing evidence indicating an association between invasive non-typeable Haemophilus influenzae (NTHi) infection in pregnancy and early pregnancy loss. As the diagnosis relies on microbiological investigation of postmortem placental and foetal samples, a significant proportion of NTHi-related pregnancy loss remains unrecognised. To better characterise NTHi in septic abortion, we report NTHi cases associated with early pregnancy loss. Methods We reviewed all post-mortems at <24 weeks gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Early-onset neonatal NTHi infections are well described in studies from Europe (197)(198)(199), the United States (200), and Australia (201), with an incidence of 0.9/100,000 (95% CI, 0.9 to 1.6) in infants born at term rising to 342/100,000 (95% CI, 234 to 483) in infants born at ,28 weeks gestation (104,197,199,202) accounting for approximately 5% of all neonatal sepsis episodes (104). The European EU-IBIS study reported a 10-foldhigher incidence of invasive NTHi disease than with Hib in neonates, with 81% of cases occurring in the first 7 days of life (9).…”
Section: Nthi Infections In Neonates and Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Early-onset neonatal NTHi infections are well described in studies from Europe (197)(198)(199), the United States (200), and Australia (201), with an incidence of 0.9/100,000 (95% CI, 0.9 to 1.6) in infants born at term rising to 342/100,000 (95% CI, 234 to 483) in infants born at ,28 weeks gestation (104,197,199,202) accounting for approximately 5% of all neonatal sepsis episodes (104). The European EU-IBIS study reported a 10-foldhigher incidence of invasive NTHi disease than with Hib in neonates, with 81% of cases occurring in the first 7 days of life (9).…”
Section: Nthi Infections In Neonates and Pregnancymentioning
confidence: 99%
“…Each additional gestational week reduced the CFR by 21% (OR, 0.79; 95% CI, 0.69 to 0.90). NTHi can colonize the female genital tract, and an ascending infection can cause both maternal and fetal infection, with maternal sepsis, septic abortion, preterm delivery, and increased complications during labor as possible consequences (196,198,203). In the EU-IBIS study, for example, NTHi caused more infections in women than in men aged 25 to 44 years, and there may be an increased risk of invasive NTHi infection in women of childbearing age.…”
Section: Nthi Infections In Neonates and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis relies on the microbiological investigation of placental and foetal samples, and a significant proportion of Haemophilus-related preterm delivery or pregnancy loss may go unrecognised. A study from Scotland in 2017-2018 reviewed all post-mortems at <24 weeks gestation with histologically proven acute chorioamnionitis on placental histology; H. influenzae accounted for 20% of infections associated with early pregnancy loss prior to week 24 [28]. The inconsistent definition, or reporting, of invasive H. influenza infections in pregnancy is apparent from the contrasting numbers of bacteraemia, from 100% in the US ABC catchment areas 2008-2019 [7] to 34% in the New Zealand study [8].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, H. influenzae has not been recognized as a leading cause of intraamniotic infection (IAI) ( 12 ). However, recent case reports describe IAI that showed histologic evidence of acute necrotizing chorioamnionitis, suggesting that maternal H. influenzae infection can involve the amniotic cavity and the fetus ( 13 ).…”
mentioning
confidence: 99%